Ecclesiality and Human Socialization in the Aspect of Applied Theology - Jan Kazimierz Przybyłowski (The Francis de Sales Scientific Society (TNFS.PL), 2022)
Applied theology is the scientific reflection on the daily "growth" of man, who lives every day in the world and there fulfils himself and realizes his existential vocation, and Christians build the Kingdom of God. From the perspective of applied theology, three main principles can be distinguished that link ecclesiology and socialization: respect for truth, social justice and charity. In applied theology, it is possible to undertake scientific reflection on ecclesiology without violating pastoral theology's right to study the Church and its salvific mission. However, in the search for knowledge about the dimensions of human social life, authoritarian and abstract universalism should be avoided.